الحماية القانونية لحقوق الملكية الفكرية في التشريع الإماراتي: جمارك دبي – نموذجاً: Legal Protection of Intellectual Property Rights in UAE Legislation: Dubai Customs – A model - AlMatri, Ghenaa Musaed Mohamed; Abdul Samad Musa (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث هدفت الدراسة إلى معرفة الملكية الفكرية وصورها، وبيان الإطار القانوني الوطني لحماية حقوق الملكية الفكرية من خلال التعرف على دور وآليات جمارك دبي في حماية حقوق الملكية الفكرية، والدور التشريعي والقضائي في دولة الإمارات لحماية حقوق الملكية الفكرية، وتأتي إشكالية البحث في توفير الحماية القانونية للملكية الفكرية والابتكارات الجديدة وبراءة الاختراع وصيانتها من استغلال الآخرين لها، والتي مازالت التشريعات القانونية تقوم بحمايتها من التعسف وانتهاك حقوقها. اعتمدت الباحثة على المنهج الوصفي التحليلي والتأصيلي الذي يعتمد على الضوابط البحثية المحددة للوقوف على وصف الظاهرة وصفاً دقيقاً من خلال دراسة القوانين والتشريعات في دولة الإمارات العربية المتحدة، والتحليل الدقيق للحقائق الجزئية والملاحظات المتعمقة للظواهر الواقعية، وتوصلت الباحثة الى العديد من النتائج أهمها أن الحقوق القانونية لحماية الملكية الفكرية في دولة الإمارات تشمل براءات الاختراع والعلامات التجارية وحقوق التأليف والنشر والتصاميم، وبما يسمح للمبدع ومالك العلامة التجارية وبراءة الاختراع وحق المؤلف بالاستفادة من عمله وتعبه واستثماره. وكذا بيان دور جمارك دبي في هذا حماية حقوق الملكية الفكرية وفي منع انتشار البضائع المزيفة، والتوصل الى توصيات جديدة يستفاد منها تكون نواه مستقبلاً للباحثين. ABSTRACT The study aimed to learn about intellectual property and its forms and to explain the national legal framework for protecting intellectual property rights by identifying the role and mechanisms of Dubai Customs in protecting intellectual property rights, and the legislative and judicial role in the UAE in protecting intellectual property rights. The problem of research comes in providing legal protection for intellectual property, innovations, and patents, and maintaining them from exploitation by others, which legal legislation is still protecting from abuse and violation of their rights. The researcher relied on the descriptive, analytical, and original approach, which relies on specific research controls to accurately describe the phenomenon through studying the laws and legislation in the United Arab Emirates, careful analysis of partial facts, and in-depth observations of real-life phenomena. The researcher reached many results, the most important of which is that the legal rights to protect intellectual property in the UAE include patents, trademarks, copyrights, and designs, allowing the creator and owner of the trademark, patent, and copyright to benefit from his work, effort, and investment. As well as explaining the role of Dubai Customs in protecting intellectual property rights and preventing the spread of counterfeit goods, and coming up with new recommendations that will be useful to researchers in the future.